Indonesia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Indonesia during the 1990s. The adjustment effort during 1991/92-1992/93 was marked by a tightening of monetary policy, and measures were also taken to curb new external borrowing. Interest rates rose sharply, as large amounts of central bank debt certificates were placed with the domestic banking system and Bank Indonesia sharply curtailed its foreign exchange swap operations. The expansion in domestic demand gained momentum during 1994/95, rising in real terms by 9 percent.